COMPARATIVE ANALYSIS OF PHYSICAL EDUCATION SYLLABUS FOR JUNIOR SCHOOL AGE IN SOME EUROPEAN COUNTRIES - Miloš Marković; Dragan Branković; Milovan Ljubojević; Dragoljub Višnjić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2012)
In European countries' pedagogical-educational systems physical education is present as a class that is supposed to contribute to integral personality development. Physical education classes are still the most organized mass system for engaging kids and young people in physical activities, through which certain influence on the organism is made. For a long sequence of years there are indications of certain changes in physical education classes as part of educational reforms in countries undergoing transition. Therefore there is possibility for innovation, improvement and further perfection of existing physical education classes syllabi in accordance with the needs of students and the society. Until now syllabi have been improved, changed and then applied without taking into account elements of physical education syllabi based on the quality analysis. In this paper comparative analysis of physical education syllabus for junior school age was performed for the following countries: England, Russia, Greece, Switzerland, Montenegro and Serbia. The following was analyzed and compared: physical education's goal and tasks, educational contents, number of physical education classes in the syllabus, method of syllabus realization as well as working forms through which physical education syllabi are realized. Through this analysis gave a conclusion was reached that the similarities and differences of existing syllabi can ease the reformation of physical education in the future, in case a societal need for that arises.